Acute necrotizing pancreatitis complicating as Fournier’s gangrene - Anand, Gautam; Nagpal, Ashutosh; Sharma, Deborshi (International Surgery Journal, 2022)
Scrotal involvement is extremely rare complication of acute necrotising pancreatitis. It presents as scrotal swelling and skin color change, which mimics the presentations of testicular torsion, epididymitis, and testicular tumor. Early diagnosis can significantly reduce the associated mortality both with necrotising pancreatitis and Fournier gangrene. Thorough clinical examination along with abdominopelvic Computed Tomography provides a useful means of diagnosing this complication. Here, we are presenting a case of acute necrotising pancreatitis with collection in left pararenal space tracking all the way to reach the left inguinal canal till the root of scrotum, being managed successfully after early diagnosis with early debridement and application of vacuum assisted drainage.